Identification of RNA bound to the TDP-43 ribonucleoprotein complex in the adult mouse brain. Issue 4 (May 2013) - Narayanan, Ramesh K.; Mangelsdorf, Marie; Panwar, Ajay; Butler, Tim J.; Noakes, Peter G.; Wallace, Robyn H.
Abstract: Cytoplasmic inclusions containing TDP-43 are a pathological hallmark of several neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS) and frontotemporal dementia. TDP-43 is an RNA binding protein involved in gene regulation through control of RNA transcription, splicing and transport. However, the function of TDP-43 in the nervous system is largely unknown and its role in the pathogenesis of ALS is unclear. The aim of this study was to identify genes in the central nervous system that are regulated by TDP-43. RNA-immunoprecipitation with anti-TDP-43 antibody, followed by microarray analysis (RIP-chip), was used to isolate and identify RNA bound to TDP-43 protein from mouse brain. This analysis produced a list of 1839 potential TDP-43 gene targets, many of which overlap with previous studies and whose functions include RNA processing and synaptic function. Immunohistochemistry demonstrated that the TDP-43 protein could be found at the presynaptic membrane of axon terminals in the neuromuscular junction in mice. In conclusion, the finding that TDP-43 binds to RNA that codes for genes related to synaptic function, together with the localization of TDP-43 protein at axon terminals, suggests a role for TDP-43 in the transport of synaptic mRNAs into distal processes.